A hybrid quantum evolutionary algorithm with cuckoo search algorithm for QoS multicast routing problem. (21st February 2019) - Meraihi, Yassine; Ramdane-Cherif, Amar; Mahseur, Mohammed; Acheli, Dalila
The QoS multicast routing problem is one of the most interesting combinatorial optimisation problems for transmission in the areas of networks and distributed systems. It is known to be an NP-hard problem, so many heuristic algorithms have been employed to solve this problem. This paper proposes two-hybrid approaches based on the hybridisation of cuckoo search (CS) algorithm with quantum evolutionary algorithm (QEA) to solve the quality of service (QoS) multicast routing problem. The main idea of the first approach, named CSQEA1, is the integration of the evolutionary equation of CS in the evolutionary operator of QEA, the rotation angle of quantum gates is adjusted by the evolution equation of CS; while the main idea of the second approach, named CSQEA2, is the replacement of the evolutionary equation of QEA by the evolutionary equation of CS, the rotation angle is used to encode the new Q-bit. The aim of these approaches is to avoid the premature convergence, ensure the diversity of the solutions and improve the effectiveness and the robustness of QEA. The simulation results show the successfulness and the efficiency of our proposed algorithms compared with other existing algorithms in the literature.